Routledge handbook of strength and conditioning sport-specific programming for high performance - Turner, Anthony (Routledge, Taylor & Francis Group, 2018)
Drawing on the latest scientific research, this handbook introduces the essentials of sport-specific strength and conditioning programme design for over 30 different sports. Enhanced by extensive illustrations and contributions from more than 70 world-leading experts, its chapters present evidence-based best practice for sports including football, rugby, tennis, hockey, basketball, rowing, boxing, golf, swimming, cycling and weightlifting, as well as a variety of wheelchair sports.